Effects of high-intensity functional training and circuit resistance training on the serum levels of IFN-γ in obese women - Samaneh Jadidi; Seyed Mohsen Avandi; Ali Khaleghian (Jorjani Biomedicine Journal, 2023)
Samaneh Jadidi, Seyed Mohsen Avandi , Ali Khaleghian Background: Obesity is one of the most serious health problems associated with inflammation. It has been found that functional and resistance physical activities improve obesity and inflammation. The aim of this study was to investigate the effect High-intensity Functional training (HIFT) and Circuit resistance training (CRT) on serum levels of the pro-inflammatory factor interferon gamma (IFN-γ) in obese women. Methods: Thirty-six obese women of Semnan city (age: 32.66 ± 3.91, weight: 86.97± 9.08 and BMI> 30) were selected and divided into three groups of HIIF (n =12), CRT (n = 12) and control (n = 12) were divided. HIIF was performed in the form of cross-fit exercises and Circuit exercises in the form of weight training for 6 weeks. Finally, the IFN-γ was measured using the Human IFN-g Elisa kit 96t-zellbio. To examine the data, one-way analysis of variance and dependent t-test at the level of p≤0.05 were used and all calculations were performed using SPSS software version 24. Results: The results showed that there was no significant change in IFN-γ level in training groups compared to before training (P>0.05). Also, the results between groups did not show a significant difference in serum IFN-γ between HIIF and CRT (P>0.05). Conclusion: Therefore, it seems that of exercise does not affect the dependent variable of serum interferon gamma levels.